2002
DOI: 10.1046/j.1365-2222.2002.01524.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of current asthma and active smoking effect among the elderly

Abstract: The prevalence of current asthma is common among the elderly, and active smoking may play an important role in the development of asthma and bronchial hyper-responsiveness among the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 26 publications
(30 reference statements)
6
63
1
5
Order By: Relevance
“…Outra possível explicação é o fato de que as mulheres, de um modo geral, referem mais sintomas do que os homens. Essas explicações teóricas acerca das associações da doença com o sexo feminino também podem ser estendidas aos indivíduos com idade avançada, uma vez que o declínio funcional pulmonar que ocorre com a idade, associado à co-existência de outras morbidades, torna este grupo etário particularmente mais consensioso dos sintomas respiratórios, fato nem sempre descrito em pesquisas clínicas 6 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Outra possível explicação é o fato de que as mulheres, de um modo geral, referem mais sintomas do que os homens. Essas explicações teóricas acerca das associações da doença com o sexo feminino também podem ser estendidas aos indivíduos com idade avançada, uma vez que o declínio funcional pulmonar que ocorre com a idade, associado à co-existência de outras morbidades, torna este grupo etário particularmente mais consensioso dos sintomas respiratórios, fato nem sempre descrito em pesquisas clínicas 6 .…”
Section: Resultsunclassified
“…Tal fenômeno, muito provavelmente relaciona-se à maior exposição aos fatores de risco ambientais 4 , tais como alergênios 1 , aumento da poluição atmosférica 5 , variações climáticas e tabagismo 6 . Nesse sentido, torna-se necessá-rio o desenvolvimento de protocolos, visando a definir, de forma confiável e precisa, a incidência e prevalência da doença e apontar possíveis fatores de risco.…”
Section: Introductionunclassified
“…(3) In a study involving adolescents, (12) the development of symptoms suggestive of asthma over a 6-year observation period was found to be associated with three independent risk factors: bronchial hyperresponsiveness to methacholine, atopy and smoking. In another study, (13) smoking was considered a risk factor for asthma, especially in individuals over 55 years of age.…”
mentioning
confidence: 99%
“…(15)(16)(17)(18) The fact that the questionnaire had already been translated into Portuguese, and that the information brought to light through its use was equivalent to that of the European Community Respiratory Health Survey justified our decision to use this instrument. By comparing our results to those of the validation study conducted by Solé et al (1998), we observed similar sensitivity and specificity for the proposed method.…”
Section: Discussionmentioning
confidence: 99%